2011
DOI: 10.1007/s00592-011-0287-8
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of common carotid arterial diameter with atherosclerosis and diabetic retinopathy in patients with type 2 diabetes mellitus

Abstract: The clinical significance of the diameter of the common carotid artery (CCA) measured ultrasonographically in diabetic practice has not been sufficiently established. The objective of this study was to investigate the relationship of the ultrasonic CCA diameter with atherosclerotic measures and diabetic retinopathy as a microvascular complication in patients with type 2 diabetes mellitus (T2DM). This hospital-based cross-sectional study included 102 patients with T2DM (men: 65%, mean age: 57 years) who had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
18
1
2
Order By: Relevance
“…[30][31][32] CCA-diameter is thought to be an adequate measure for determining the extent of systemic atherosclerosis. 33 Our results may support incidental findings of CAC on panoramic radiographs as a useful marker for systemic atherosclerosis.…”
Section: Discussionsupporting
confidence: 81%
“…[30][31][32] CCA-diameter is thought to be an adequate measure for determining the extent of systemic atherosclerosis. 33 Our results may support incidental findings of CAC on panoramic radiographs as a useful marker for systemic atherosclerosis.…”
Section: Discussionsupporting
confidence: 81%
“…In support of this, Krizova et al recently demonstrated that increased intra-vitreous levels of UA may be involved in the pathogenesis and progression of DR [35]. Moreover, micro and macrovascular complications cluster; DR is associated with atherosclerosis [36] and cardiorenal complications remain strongly interrelated in diabetes [37], suggesting possible common underlying risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the frequency of patients with the plaque ≥2 according to the presence of DR was not significantly different. Miyamoto et al [31] reported that mean CIMT and plaque score were not significantly correlated with DR. Rema et al [18] explained that one of the causes showing discrepancy about association DR with carotid atherosclerosis is by the differences in the ages of the populations studied (Atherosclerosis Risk in Communities study, 51 to 72 years of age; CHS, 69 to 102 years of age; our present study, 31 to 86 years of age). The other potential reasons for the discrepant results may include different sample sizes and population characteristics.…”
Section: Discussionmentioning
confidence: 99%